WILL COMMUNICATIVE LANGUAGE TEACHING WORK? TEACHERS’ PERCEPTIONS TOWARD THE NEW EDUCATIONAL REFORM IN SOUTH KOREA - Lee, Moon Woo (Universitas Pendidikan Indonesia, 2014)
Abstract: This study examines how Korean elementary and secondary school teachers perceive the seventh national curriculum focusing on communicative language teaching. Thirty-seven participants were surveyed with a questionnaire designed grounded in Li (1998) and interviewed individually for about 15-20 minutes. The collected data was analyzed based upon Stake’s (2000) theme-based approach. The results showed that teachers’ perception onto CLT was very limited to speaking skills. The main issue concerning the teachers coming from different school levels was varied. Elementary school teachers were more concerned about enhancing students’ involvement, whereas secondary school teachers pointed out the difficulty of implementing CLT due to the heavy focus on the paper-and-pencil format of college entrance exam. In addition, novice teachers were more skeptical than experienced ones in terms of the feasibility of CLT in the actual classroom context, even though they were thought to be more familiar to the concept of CLT. This study is expected to provide us with an opportunity to revisit a decade-old concept of CLT in Korean context in more critical way. Keywords: communicative language teaching, curriculum, teachers’ perception, language policy AKANKAH PENGAJARAN BAHASA KOMUNIKATIF BERHASIL? PERSEPSI-PERSEPSI GURU TERHADAP REFORMASI PENDIDIKAN BARU DI KOREA SELATAN Abstrak: Kajian ini meneliti bagaimana guru-guru sekolah dasar dan menengah Korea memahami kurikulum nasional ketujuh yang berfokus pada pengajaran bahasa komunikatif. Tiga puluh tujuh peserta dijajaki pendapatnya dengan sebuah angket yang dirancang berdasarkan temuan Li (1998) dan diwawancara satu per satu selama sekitar 15-20 menit. Data yang dikumpulkan dianalisis berdasarkan pendekatan berbasis tema oleh Stake (2000). Hasilnya menunjukkan bahwa persepsi guru terhadap Pengajaran Bahasa komunikatif (Communicative Language Teaching/CLT) sangat terbatas pada keterampilan-keterampilan berbicara. Masalah utama yang berhubungan dengan latar belakang sekolah guru yang berbeda-beda sangat beragam. Guru-guru sekolah dasar lebih memperhatikan peningkatan keterlibatan siswa, sementara guru-guru sekolah menengah menyebutkan kesulitan penerapan CLT karena fokus yang sangat besar pada format ujian tertulis masuk universitas. Selain itu, para guru pemula lebih skeptis dibanding yang berpengalaman dalam hal keterlaksanaan CLT dalam konteks kelas yang sebenarnya, meskipun mereka dianggap lebih mengenal konsep CLT. Kajian ini diharapkan bisa memberikan kesempatan bagi kita untuk mengkaji ulang konsep CLT yang sudah berumur satu dekade dalam konteks Korea dengan lebih kritis.Katakunci: Pengajaran Bahasa komunikatif (CLT), kurikulum, persepsi guru, kebijakan bahasa